Geotechnology applied to estimate soil loss by water erosion - Oliveira, Francienne Gois; Borja, Manuel Esteban Lucas; Seraphim, Odivaldo José [UNESP] (My University, 2015)
Water erosion is a major environmental problem that may compromise agricultural areas and the volume of water in a watershed. This paper presents the estimated soil loss in a watershed using Equation Revised Universal Soil Loss- RUSLE applied to a geographic information system. The factors of the RUSLE, rainfall erosivity (R), soil erodibility (K), topographic (LS), use factors and management conservation practices (CP) were obtained separately and used existing data that has been conducted in the region. In determining the potential erosion of Natural, we used the RKLS factors. All factors were generated and processed in a GIS. The results were obtained by means of maps and were satisfactory. Soil losses, predominately “Low” class, ranked among 0-10 t ha-1 yr-1. The GIS proved to be feasible in the determination of the various factors of Universal Soil Loss Equation, making possible zoning areas with high soil losses and high erosion potential.
Keywords: Geographic information system; Soil conservation; Universal equation of soil loss